MDM2 suppresses c-Myc synthesis by binding to the 5’ mRNA translation regulatory sequence - Justine Habault; Norman Salomao; Lixiao Wang; Laurence Malbert-Colas; Chrysoula Daskalogianni; Sivakumar Vadivel Gnanasundram; Mitesh Dongre; Marzia Spagnardi; Lucia Martinkova; Sa Chen; Lenka Hernychová; Lucas Robidas; et al. (Proceedings of the National Academy of Sciences, 2026)
The p53 tumor suppressor and the c-Myc oncogene are among the most frequently deregulated genes in human cancers, yet the molecular cross talk between these pathways remains poorly understood. MDM2 is a key negative regulator of p53 and a target for emerging cancer therapies designed to activate p53. Likewise, targeting c-Myc is a long-standing but challenging goal in cancer therapy. Here, we report that the small MDM2-binding drug Milademetan promotes an interaction between MDM2 and the 5’ untranslated region of the c-Myc mRNA, causing a suppression of c-Myc mRNA translation without affecting c-Myc RNA levels. The interaction also occurs under nonproliferative conditions in the absence of drug. Milademetan-mediated c-Myc depletion is accompanied by the induction of apoptosis and suppression of cell proliferation and prevents tumor growth, independently of p53 status. These findings reveal an unexpected mechanism by which MDM2 coordinates two of the most frequently altered pathways in cancer and provide a rationale for targeting c-Myc-driven tumors, including those lacking functional p53, through MDM2 modulators.